2020
DOI: 10.1039/d0nr03951a
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalates encapsulated into hollow double-shelled nanospheres as amphiphilic nanoreactors for an effective oxidative desulfurization

Abstract: Although some catalytic hollow nanoreactors have been fabricated, the encapsulated active species focus on metal nanoparticles and the method for polyoxometalate (POM)-containing hollow nanoreactors is seldom developed. Herein, we reports...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…To get insight into the effect of the (Gly) 3 PMo 12 O 40 @MnFe 2 O 4 hybrid dosage on the Cat‐ODS process, the catalytic oxidation tests were developed in the catalyst dosage range of 0‐0.12 g (Figure 7). As expected, the Cat‐ODS efficiency of all types of organosulfur compounds in MFOs was sharply increased after increasing the catalyst dosage from 0.03 to 0.10 g. It is caused by the high production of oxoperoxo‐metal complexes in the reaction medium 48‐51,53 . These highly reactive complexes are the key intermediates in the conversion of Th, BT, and DBT molecules to their corresponding sulfoxides and sulfones.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…To get insight into the effect of the (Gly) 3 PMo 12 O 40 @MnFe 2 O 4 hybrid dosage on the Cat‐ODS process, the catalytic oxidation tests were developed in the catalyst dosage range of 0‐0.12 g (Figure 7). As expected, the Cat‐ODS efficiency of all types of organosulfur compounds in MFOs was sharply increased after increasing the catalyst dosage from 0.03 to 0.10 g. It is caused by the high production of oxoperoxo‐metal complexes in the reaction medium 48‐51,53 . These highly reactive complexes are the key intermediates in the conversion of Th, BT, and DBT molecules to their corresponding sulfoxides and sulfones.…”
Section: Resultssupporting
confidence: 51%
“…Interestingly, among the different Keggin‐type POMs, it can be noted that the phosphorus‐centered structures have a tremendous potential to be more active than their silicon analogs due to the formation of more stable oxoperoxo‐metal complexes in Cat‐ODS reactions 53 . By comparing the results of the current survey with earlier literature, it can be also concluded that the synthesized (Gly) 3 PMo 12 O 40 @MnFe 2 O 4 hybrid nanocomposite shows the extraordinary performance in the oxidation of Th, BT, and DBT under the mild reaction conditions (at the temperature of 35°C and reaction time of 60 minutes) 6,20,39,48‐51 …”
Section: Resultsmentioning
confidence: 58%
“…Similarly, Liu et al (2020) have observed that POM catalyst alone, due to its hydrophilicity, could not properly contact DBT (which is lipophilic). Thus, much better interaction between DBT and catalyst was observed by covering the POM catalyst with a hydrophobic carbon layer, significantly increasing the reaction rate [140]. In another approach, Yu et al (2020) immobilized lipophilic C 12 PW on hydrophilic g-C 3 N 4 , thus increasing the utilization of hydrogen peroxide and the contact between DBT and active sites [141].…”
Section: Amphiphilic Carbonsmentioning
confidence: 99%
“…Polyoxometalates (POMs) are molecularly defined metal oxide clusters comprising high valent early transition metals bridged by oxygen atoms. In general, POMs are anionic clusters that exhibit various topologies, including Keggin ([XM 12 O 40 ] n − ), Dawson ([X 2 M 18 O 62 ] n − ), and Anderson ([XM 6 O 24 ] n − ) types, where X is typically an octahedral template for the Anderson family and a tetrahedral template for the other two, and M is typically Mo or W . Their strong Brønsted acidity and reversible multielectron redox properties make them excellent catalysts for a wide range of reactions such as esterification, hydrolysis, or oxidation of organic compounds . However, POMs alone often exhibit poor reusability in these catalytic systems due to their high solubility, low surface area, and instability under certain catalytic conditions, limiting their practical implementation.…”
Section: Introductionmentioning
confidence: 99%